The association between chronic heart failure and frailty index: A study based on the National Health and Nutrition Examination Survey from 1999 to 2018 - Chen, Xiaozhe; Hou, Chunlei; Yao, Lei; Ma, Yulong; Li, Yunfeng; Li, Jianhua; Gui, Mingtai; Wang, Mingzhu; Zhou, Xunjie; Lu, Bo; Fu, Deyu (Frontiers in Cardiovascular Medicine, 2023)
Objective: To explore the association between frailty index and chronic heart failure (CHF). Methods: We collected data from the National Health and Nutrition Examination Survey (NHANES) (1998-2018) database to assess the association between CHF and frailty. Demographic, inquiry, laboratory examinations, and characteristics were gathered to compare CHF and non-CHF groups. Multiple logistic regression analysis was performed to explore the relationship between frailty and CHF. Cox proportional hazards models were used to estimate hazard ratios (HR) and 95% confidence interval (CI) for mortality from all causes, and cardiovascular disease (CVD). Results: A total of 16,175 participants with cardiac-cerebral vascular disease were categorized as CHF (n = 1125) and non-CHF (n = 15,050) groups. In CHF patients, the prevalence of frailty, pre-frailty, non-frailty was 66.31%, 30.93% and 2.75%, respectively. In multiple logistic regression, CHF patients who were male (OR =0.63, 95% CI:3.11-5.22), whose annual family income was over 20,000 (OR= 0.52, 95% CI: 0.37-0.72, p < 0.001), or with normal hemoglobin level (OR = 0.77, 95% CI: 0.68-0.88, P <0.001) had a lower likelihood of frailty. CHF patients with hypertension (OR = 3.60, 95% CI: 2.17-5.99, P <0.0001), coronary heart disease (OR = 1.76, 95% CI: 1.10-2.84, P =0.02), diabetes mellitus (OR = 1.89, 95% CI: 1.28-2.78, P <0.001) and stroke (OR = 2.52, 95% CI: 1.53-4.15, P <0.001) tended to be frail. Survival analysis suggested that prefrailty and frailty were related to poor all-cause deaths (HR=1.48, 95% CI:1.36-1.66; HR=2.77, 95% CI:2.40-3.18) and CVD mortality (HR=1.58, 95% CI:1.26-1.97; HR=2.55, 95% CI:2.02-3.21). CHF patients with frailty was strongly connected with all-cause death (HR=2.14, 95% CI:1.27-3.62). Conclusion: Frailty was positively associated with CHF. CHF patients who were male, whose annual family income was over 20,000 or with normal hemoglobin level were negatively correlated to frailty. For cardia-cerebrovascular as well as CHF patients, frailty was strongly connected with all-cause death.